A Watt-Level Pulsed Er:Lu2O3 Laser Based on a TiB2 Saturable Absorber - Yangyang Liang; Lu Zhang (Nanomaterials, 2024)
TiB2 nanoparticles with a bandgap of 0 eV were prepared, and the corresponding nonlinear optical response at 2.85 μm was investigated. Employing a TiB2 as a saturable absorber, a 2.85 μm pulsed Er:Lu2O3 crystal laser with an average output power of 1.2 W was achieved under a maximum pump power of 9.51 W. Laser pulses with durations of ~203 ns were delivered at a repetition rate of 154 kHz, which corresponds to a pulse energy of ~7.8 µJ and a peak power of 39.3 W. As far as we know, the result represents the highest average output power from all Q-switched Er:Lu2O3 crystal lasers.